HIGH EDUCATION IN THE PROCESSES OF GLOBALIZATION (PHILOSOPHICAL ANALYSIS) - Живага, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Actual questions of transformation of the system of high education in conditions of globalization applied to Ukraine are examined.